Harvesting liquid stream energy from unsteady peristaltic flow induced pulsatile Flow-TENG (PF-TENG) using slipping polymeric surface inside elastomeric tubing. (November 2019) - Cheedarala, Ravi Kumar; Shahriar, M.; Ahn, Jee Hwan; Hwang, Jeong Yun; Ahn, Kyoung Kwan
Abstract: Flow in small size tubing or channels in multidisciplinary field such as Chemistry, medical and lab on chip sensors can be a potential candidate for energy scavenging. Recently, energy harvesting techniques have been developed utilizing the steady flow under induced pressure gradient in lab on chip device. Here, for the first-time harnessing energy from unsteady pulsatile water flow over hydrophobic polymeric surface attached in the inner wall of the elastic tubing that induces slip boundary and causes electrostatic potential difference in the electrical double layer of the solid-liquid interface is described. This work demonstrates peristaltic flow driven triboelectric nano-generator based on the flow contact electrification between the hydrophobic micro porous PVDF (mpPVDF) membrane and water stream flowing through elastic silicon tubing. The efficiency of the PF-TENG as energy harvester was evaluated using deionized water (PF.DIw-TENG), tap water (PF.Tw-TENG). The mechanistic approach is discussed for the generation of alternating current based on the relation between the hydrodynamics of pipe flow and adsorbed ions at the Electrical Double Layer (EDL). The generated voltage and short-circuit currents (Isc ) are superior in PF.Tw-TENG, in particular, the maximum peak to peak values of voltage and Isc are 20.93 V and 1.67 μA, respectively, over PF.DIw-TENG. The PF.Tw-TENG shows greater efficiency over PF.DIw-TENG due to the presence of dissolved free mobile ions which can enhance the power output. Moreover, we verify the possibility of the PF-TENG as self-powered average volumetric flow rate sensor. The developed PF.TENG can be potentially applied for fluid dynamic monitoring of peristaltic flow involved in pharmaceuticals and food industries. Graphical abstract: Image 1 Highlights: A novel PF-TENG utilizing unsteady peristaltic flow to harness liquid stream energy has been proposed. The PVDF membrane was used as slipping surface in the elastomeric tubing. AC current generation due to the triboelectrification from the induced pulsatile has been investigated. Maximum power density has been achieved up to 25.63 mW/m 2 for tap water.